2022
DOI: 10.2196/35951
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Health-Related Quality of Life With Multimodal Data: Viewpoint

Abstract: The ability to objectively measure aspects of performance and behavior is a fundamental pillar of digital health, enabling digital wellness products, decentralized trial concepts, evidence generation, digital therapeutics, and more. Emerging multimodal technologies capable of measuring several modalities simultaneously and efforts to integrate inputs across several sources are further expanding the limits of what digital measures can assess. Experts from the field of digital health were convened as part of a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The use of wearable technology (e.g., chest straps, ear lobe sensors, wristbands, patches) provides exiting opportunities for delivering continuous (as opposed to episodic) feedback and for interventions on outcomes relevant to the individual. Several systematic reviews showed that wearable technology can have a positive impact on sleep, stress, physical activity, depression, emotional regulation, and cardiovascular and metabolic functioning ( 14 , 20 , 24 30 ). Sleep, stress and physical activity are considered transdiagnostic markers of psychiatric problems ( 18 20 ), and can be monitored relatively easy with wearable technology, assuming that the algorithms are accurate and robust ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of wearable technology (e.g., chest straps, ear lobe sensors, wristbands, patches) provides exiting opportunities for delivering continuous (as opposed to episodic) feedback and for interventions on outcomes relevant to the individual. Several systematic reviews showed that wearable technology can have a positive impact on sleep, stress, physical activity, depression, emotional regulation, and cardiovascular and metabolic functioning ( 14 , 20 , 24 30 ). Sleep, stress and physical activity are considered transdiagnostic markers of psychiatric problems ( 18 20 ), and can be monitored relatively easy with wearable technology, assuming that the algorithms are accurate and robust ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these biomarkers, recommender systems might provide recommendations for personalized interventions, which will have significant impact on the use of the technology in healthcare and the relationship between patients and their healthcare professional ( 21 23 ). Recent meta-analyses have resulted in small to medium effect sizes of wearable technology, including fitness trackers, activity trackers and biofeedback devices on stress, sleep, physical activity, depression, emotional and behavioral self-regulation, cardiovascular functioning, and metabolic syndrome ( 14 , 16 , 20 , 24 31 ). However, the implementation of wearable technology in forensic psychiatry faces challenges, including limited technology readiness, acceptance, usability of the devices, continuous use of the devices, privacy concerns and data management ( 14 , 32 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Digital health is rapidly evolving and expanding, powering a paradigm shift in evidence generation for clinical development and care delivery (Marra et al, 2020 ). Driven by advances in cutting-edge biosensors and multi-sensor wearable devices, increasing maturity and acceptance of remote clinical trial models (Izmailova et al, 2021 ) and digital therapeutics (Stern et al, 2022 ) and huge growth in computational approaches to processing and interpreting this digital health data, there is great excitement in the field about the possible applications of multimodal digital approaches (Clay et al, 2022 ). Multimodal data has particular relevance to addressing complex measurement concepts and to development of better personalized treatment, incorporating digital and behavioral phenotyping with molecular endotyping.…”
Section: Introductionmentioning
confidence: 99%